Analisis Karakteristik Parkir pada Supermarket di Kota Makassar - Radjawane, Louise Elizabeth; Pratama, Yudhistira Fiska; Tanan, Benyamin (Universitas Ibn Khaldun, 2024)
Parking space is one of the main problems of increasing the economy in urban areas. This is also the impact of the development of transportation facilities and infrastructure. One of the areas that provide parking space is in trade areas such as shops or supermarkets. This study aims to determine the availability of parking space at the Carrefour Tamalanrea Supermarket. The method used in the analysis is the 1996 Technical Guidelines for the Implementation of Parking Facilities. The results of this study are the availability of parking spaces in the Carrefour Tamalanrea Supermarket area based on the existing Parking System Scheme, namely 40 parking space unit for car parking and 50 parking space unit for motorbikes. Parking characteristics of The Supermarket are the largest parking area provided for cars is 465m2 and 78m2 for motorcycles, provision of the most parking space for cars and motorcycles, namely 853 parking space unit and 958 parking space unit, the highest parking duration occurred on Monday for cars, namely 0.73 and motorcycles, 0.9 on Saturdays. The highest parking index occurred on Sundays for motorcycles and cars, 0.78 and 0.775 respectively. Turn over rates occur on Sundays for types of cars and motorcycles, respectively 6 and 4.